Identifying selection signatures for immune response and resilience to Aleutian disease in mink using genotype data - Hu, Guoyu; Do, Duy Ngoc; Manafiazar, Ghader; Kelvin, Alyson A.; Sargolzaei, Mehdi; Plastow, Graham; Wang, Zhiquan; Davoudi, Pourya; Miar, Younes (Frontiers in Genetics, 2024)
Aleutian disease (AD) brings tremendous financial losses to the mink industry. Selecting AD-resilient mink has been conducted to control AD. Such selections could have altered the patterns of genetic variation responding to selection pressures. This study aimed to identify selection signatures for immune response (IRE) and resilience to AD. A total of 1,411 mink from an AD-positive facility were used. For IRE, 264 animals were categorized according to the combined results of enzyme-linked immunosorbent assay (ELISA) and counterimmunoelectrophoresis (CIEP). For resilience, two grouping methods were used: 1) general resilience performance (GRP, n=30) evaluated based on feed conversion ratio, Kleiber ratio, and pelt quality, and 2) female reproductive performance (FRP, n=36) measured based on the number of kits alive 24h after birth. Detection methods were pairwise fixation index, nucleotide diversity, and cross-population extended haplotype homozygosity. A total of 619, 569, and 526 SNPs were identified as candidates for IRE, GRP, and FRP, respectively. The annotated genes were involved in immune system process, growth, reproduction, and pigmentation. Two olfactory-related gene ontology (GO) terms were significant (q<0.05) for all traits, suggesting the impact of AD on the sense of smell of infected mink. Differences in detected genes and GO terms among different color types for IRE indicated variations in immune response to AD among color types. The mitogen-activated protein kinase (MAPK) signaling pathway was significant (q<0.05) for FRP, suggesting that AD may disrupt MAPK signaling and affect FRP. The findings of this research contribute to our knowledge of the genomic architecture and biological mechanisms underlying AD resilience in mink.